Investigating the Influence of Computer Anxiety on the Academic Performance of Junior Secondary School Students in Computer Studies in Nigeria - Oribhabor, Chinelo Blessing (International Journal of Computing Sciences Research, 2020)
Purpose – This study examined the influence of computer anxiety on the academic performance of junior secondary school students (JSS) in Computer Studies in Nigeria. The study specifically examined whether there is any correlation between the computer anxiety of students and their performance in Computer Studies. Method – The sample consisted of one thousand, two hundred JSS 3 students from sixty selected secondary schools in the 12 selected states from each of the six geopolitical zones in Nigeria. The research instrument that was used in the study was computer anxiety scale which was validated by the Guidance and Counseling lecturers and Educational Measurement and Evaluation experts. Cronbach’s alpha technique was used to determine the reliability of the computer anxiety scale and 0.87 coefficient was achieved. The students’ second term results of the 2018/ 2019 session were used to measure their academic performance in Computer Studies. Independent t-test and Pearson Product Moment Correlation were used to analyze the data collected. Results – The result of the study showed that most of the students used in the study were mildly anxious when dealing with computer; there is no significant difference in the computer anxiety of male and female junior secondary school students in Nigeria; and there is a significant negative relationship between computer anxiety and Computer Studies performance of junior secondary school students’ in Nigeria. Conclusion – The study concludes that students’ anxious feelings of operating computer do negatively affect their performances in the computer studies. Recommendation – Based on the findings, the researcher recommends amongst others that Computer Studies’ teachers should indulge the students in constant use of computer for assignments and web-browsing so as to enhance their confidence and reduce anxiety in Computer Studies classroom. Practical Implication – The results of the study reflect the need for the Nigerian Government to provide enough computer sets to schools so that each students will be entitled to a computer during their training.